Spatial panel count data: modeling and forecasting of urban crimes - Stephanie Glaser; Robert C. Jung; Karsten Schweikert (Journal of Spatial Econometrics, 2022)
The steadily growing access to high-quality spatio-temporal crime count data with a high level of spatial detail allows to uncover interesting relationships between crime types within and between small regional units. Data coherent forecasting of such counts has to take the integer and non-negative nature of the data into account. Spatial panel data models that meet the criterion of coherency are relatively sparse. This paper proposes a new spatial panel regression framework with fixed effects to overcome these shortcomings. Depending on whether time dynamic effects are included in the model specification, estimation and inference are based either on a pseudo maximum likelihood method or on quasi-differenced generalized methods of moments. The models' usefulness is demonstrated in a forecasting exercise of monthly crime counts at census tract level from Pittsburgh, Pennsylvania.
Keywords: C33; C53; K42; 330; Count data; Spatial panel models; Fixed effects; Predictive modeling